Cardioprotection by ischemic postconditioning and cyclic guanosine monophosphate-elevating agents involves cardiomyocyte nitric oxide-sensitive guanylyl cyclase. Issue 6 (9th February 2018) - Frankenreiter, Sandra; Groneberg, Dieter; Kuret, Anna; Krieg, Thomas; Ruth, Peter; Friebe, Andreas; Lukowski, Robert
Abstract: Aims: It has been suggested that the nitric oxide-sensitive guanylyl cyclase (NO-GC)/cyclic guanosine monophosphate (cGMP)-dependent signalling pathway affords protection against cardiac damage during acute myocardial infarction (AMI). It is, however, not clear whether the NO-GC/cGMP system confers its favourable effects through a mechanism located in cardiomyocytes (CMs). The aim of this study was to evaluate the infarct-limiting effects of the endogenous NO-GC in CMs in vivo . Methods and results: Ischemia/reperfusion (I/R) injury was evaluated in mice with a CM-specific deletion of NO-GC (CM NO-GC KO) and in control siblings (CM NO-GC CTR) subjected to an in vivo model of AMI. Lack of CM NO-GC resulted in a mild increase in blood pressure but did not affect basal infarct sizes after I/R. Ischemic postconditioning (iPost), administration of the phosphodiesterase-5 inhibitors sildenafil and tadalafil as well as the NO-GC activator cinaciguat significantly reduced the amount of infarction in control mice but not in CM NO-GC KO littermates. Interestingly, NS11021, an opener of the large-conductance and Ca 2+ -activated potassium channel (BK), an important downstream effector of cGMP/cGKI in the cardiovascular system, protects I/R-exposed hearts of CM NO-GC proficient and deficient mice. Conclusions: These findings demonstrate an important role of CM NO-GC for the cardioprotective signalling following AMI in vivo . CM NO-GC function is essential for the beneficial effects on infarct size elicited by iPost and pharmacological elevation of cGMP; however, lack of CM NO-GC does not seem to disrupt the cardioprotection mediated by the BK opener NS11021.